Effect of flushing on reproductive performance in hair sheep in a research and teaching support center in Mexico (Revista Sistemas de Producción Agroecológicos, 2021)
Sheep production is an important change in the livestock economy in Mexico, the quality can be improved with the implementation of nutritional and biotechnological strategies. This study evaluated the effect of flushing in sheep with medium body condition (CCM) or Low (CCB) body condition on reproductive performance in a Research and Teaching Support Center in Mexico. A group of 42 multiparous sheep of Pelibuey, Dorper, Hampshire, East Friesian and Damara breeds assigned to 4 treatments T1: (N = 10 CCM with flushing), T2: (N = 9 CCM without flushing), T3: (N = 12 CCB with flushing), T4: (N = 11 CCB without flushing). The washing consists of a diet based on sorghum (Crude Protein: 14.76), weights (before, during and after the experiment). It is synchronized with a CIDR®, with withdrawal on day 9 and detected the estrus and immediate natural riding. On day 7, 1 mL of Lutalyse® (7.5 mg PGF2α) was applied. The rate of ovulation and pregnancy by ultrasonography at day 45 and 75 was evaluated, prolificity and fertility were also measured. The weighing averages were: before rinsing T1: 49.08; T2: 49.15; T3: 54.46 and T4: 52.43, during washing T1: 48.12; T2: 47.08; T3: 55.06 and T4: 50.56 and after discharge T1: 49.42; T2: 49.11; T3: 55.00 and T4: 53.63. The total averages for the 3 weighings were P1 = 51.28; P2 = 50.21; P3 = 51.79. Regarding reproductive variables, no statistically determined differences were found by means of a Z test; however, the proportions of the data that change the differences between treatments, such as: in the presentation of the estrus of T1, T3 and T4 (90, 100 and 90.4% respectively) versus T2 (55.5%); in pregnancy, T1 (60%) versus T2, T3 and T4 (44.4, 41.7 and 10% respectively) and regarding prolificacy, T1, T3 and T4 had a greater number of offspring/sheep (0.80, 1.00 and 0.90 respectively) with respect to T2 (0.33). The use of rinsing in animals with CCB and CCM before the mountain or during synchronization with pharmacological methods improves fertility; but it is important to continue supplying protein requirements to improve fertility, reduce neonatal deaths and improve the weight at birth of sheep.
Keywords: fertility; supplementation; pregnancy; prolificity; weighing